Damping Properties and Density of Helmet Liners Made of Expanded Polystyrene (EPS) - M. Trzaskalska; R. Chwastek (Archives of Metallurgy and Materials, 2020)
The purpose of the work was to determine the infuence of the bulk density ρz of granules, processing parameters and the density of ski inserts ρw made of expanded polystyrene (EPS) on their damping properties. For this aim liners for ski helmets with 3 different bulk densities were made. Sintering time and sintering pressure were also changed. The percentage damping factor η was determined on the basis of the results obtained in the rebound resilience test. Based on the analysis of the obtained data, it was found that increasing the density of EPS pads ρw increases their damping properties and at the same time contributes to a decrease in elasticity, increase in hardness and brittleness of EPS products.